2016
DOI: 10.5935/0034-7280.20160003
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive analgesia of metamizole versus ibuprofen in retinal laser photocoagulation

Abstract: Objective: To compare the effectiveness of metamizole versus ibuprofen for the reduction of pain in retinal photocoagulation (RP). RESUMOObjetivo: Comparar a efetividade da dipirona versus o ibuprofeno para a redução da dor na fotocoagulação da retina (FR). Método: Foi realizado um estudo controlado, duplo cego e randomizado englobando trinta e quatro pacientes com retinopatia diabética separados em dois grupos. Grupo A recebeu 1000mg de dipirona e o grupo B recebeu 600mg de ibuprofeno. A dor foi avaliada pela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Acute procedural pain is still a neglected phenomenon in health care (Cakmak et al, 2017;Lee, 2016;Song et al, 2018), particularly in ophthalmic procedures (Araújo et al, 2015;Castro et al, 2014;Chen et al, 2012;Chiu & Wu, 2011;Quigley et al, 2019;Ramezani et al, 2017;Santo et al, 2016). These findings corroborate our results, since most of the patients who underwent argon LRP reported pain, despite the anesthetic used, which demonstrates the nociceptive nature of the procedure.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Acute procedural pain is still a neglected phenomenon in health care (Cakmak et al, 2017;Lee, 2016;Song et al, 2018), particularly in ophthalmic procedures (Araújo et al, 2015;Castro et al, 2014;Chen et al, 2012;Chiu & Wu, 2011;Quigley et al, 2019;Ramezani et al, 2017;Santo et al, 2016). These findings corroborate our results, since most of the patients who underwent argon LRP reported pain, despite the anesthetic used, which demonstrates the nociceptive nature of the procedure.…”
Section: Discussionsupporting
confidence: 87%
“…As well as several ECRs that evaluated the pain during LRP in patients with diabetic retinopathy, our study standardized the technique of LRP, since it is unrealistic to provide number of shots with the same value for all patients undergoing LRP. In this sense, a study analyzed whether the power of the shots could influence the presence of severe pain and concluded that there is no significant difference in pain intensity (Santo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations